2015
DOI: 10.1016/j.jval.2015.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Photopheresis for Second-Line Treatment of Chronic Graft-versus-Host Diseases: Results from a Health Technology Assessment in Italy

Abstract: To develop a comparative, cost-effectiveness, and budget impact analysis of Therakos online extracorporeal photopheresis (ECP) compared with the main alternatives used for the treatment of steroid-refractory/resistant chronic graft-versus-host disease (cGvHD) in Italy. Methods: The current therapeutic pathway was identified by searching medical databases and from the results of a survey of practice in Italian clinical reference centers. A systematic review was performed to evaluate the efficacy and safety of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 64 publications
4
26
0
Order By: Relevance
“…The results of this study reflect the findings of similar studies conducted at different institutions comparing the CELLEX ® fully integrated system and multi‐step procedures used for ECP . One study reported a reduction in overall procedural times from 221 min to 145 min, while another reported a reduction from 435 min to 125 min .…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The results of this study reflect the findings of similar studies conducted at different institutions comparing the CELLEX ® fully integrated system and multi‐step procedures used for ECP . One study reported a reduction in overall procedural times from 221 min to 145 min, while another reported a reduction from 435 min to 125 min .…”
Section: Discussionsupporting
confidence: 83%
“…The results of this study reflect the findings of similar studies conducted at different institutions comparing the CELLEX ® fully integrated system and multi-step procedures used for ECP. 12,20,21 One study reported a reduction in overall procedural times from 221 min to 145 min, while another reported a reduction from 435 min to 125 min. 12,21 The CELLEX ® treatment time observed (120 min) was also similar to those recorded by a number of other units across the world (range: 91-135 min).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that the treatment of GVHD complications results in the high expenses, and one of the obstacles to ECP treatment is the substantial cost associated with this long‐term therapy . The cost of blood processing on the Sepax separator is equal to that of a conventional “off line” ECP apheresis procedure.…”
Section: Discussionmentioning
confidence: 99%